2014
DOI: 10.7551/mitpress/9542.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Nine Elements of a Sustainable Campus

Abstract: A former college president offers a framework for sustainability on campus, describing initiatives that range from renewable energy to a revamped curriculum to sustainable investment. Colleges and universities offer our best hope for raising awareness about the climate crisis and the other environmental threats. But most college and university administrations need guidance on the path to sustainability. In The Nine Elements of a Sustainable Campus, Mitchell Thomashow, a former college president,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 0 publications
0
38
0
2
Order By: Relevance
“…Most sustainable innovations have focused on the campus of a university. Here, operational innovations such as renewable energy installations, initiatives with solar arrays, wind turbines, geothermal projects, biomass production facilities, conservation retrofits, and energy efficient designs have been introduced (Thomashow, 2014). As Leal Filho et al (2015) have showed, campus greening has a clear connection with innovative projects, transfer of models for the surrounding community and the possibility to implement innovative green technologies.…”
Section: The Problems Seen In Innovation In Sustainable Development Amentioning
confidence: 99%
“…Most sustainable innovations have focused on the campus of a university. Here, operational innovations such as renewable energy installations, initiatives with solar arrays, wind turbines, geothermal projects, biomass production facilities, conservation retrofits, and energy efficient designs have been introduced (Thomashow, 2014). As Leal Filho et al (2015) have showed, campus greening has a clear connection with innovative projects, transfer of models for the surrounding community and the possibility to implement innovative green technologies.…”
Section: The Problems Seen In Innovation In Sustainable Development Amentioning
confidence: 99%
“…The primary literature chosen to create a broad framework for performing a REA was Thomashow's The Nine Principles for a Sustainable Campus [31] and the factors highlighted by Barth [23], since it focuses on practical experience and academic research. The framework included the content prepared by the Ellen MacArthur Foundation in the form of their "Towards the Circular Economy" reports [9,15,32] and "A New Dynamic: Effective Business in a Circular Economy" [33] to discover the aspects of university management overlapping with the circular economy topics.…”
Section: Rapid Evidence Assessmentmentioning
confidence: 99%
“…The evidence gathered in the REA highlighted that tackling university sustainability must include social, economic, and environmental considerations [37]. On the social side, the literature suggests that high standards for staff and students' physical and mental well-being should be reflected in university strategy and action [31,38]. It is further suggested that empowering a heightened understanding of individual and university impacts on the environment by implementing a 'good-living campus' could cause a more optimistic outlook and foster holistic approaches to environmental problem-solving [31,37,39,40].…”
Section: Rapid Evidence Assessmentmentioning
confidence: 99%
“…The events, contests and the European Platform of Universities Engaged in Energy Research, Education and Training (EPUE) are one of the main highlights together with the several multidisciplinary departments, focused on research in graduation and post-graduation. For Thomashow (2014), the campus is the adequate location to explore, build and practice this ethos. Elements established by the author are seen on the campus programs, such as EfS for qualification, photography contests and initiatives driven toward energy for sustainability.…”
Section: Campusmentioning
confidence: 99%
“…In general, the changes to the curriculums, teaching practices and research do not yet meet the demands of the global-scale problems, that require holistic approaches (Vilches 2012). Universities may be seen as laboratories to practice sustainability initiatives (Thomashow 2014).…”
Section: Introductionmentioning
confidence: 99%